2004
DOI: 10.1161/01.cir.0000139311.32278.32
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Predictors of Arrhythmic Death and Total Mortality in the Multicenter Unsustained Tachycardia Trial

Abstract: Background-Stratifiers of sudden and total mortality risk are needed to optimally target preventive therapies in patients with coronary artery disease and impaired ventricular function. We assessed the prognostic significance of ECG markers of conduction abnormalities and left ventricular hypertrophy in the Multicenter Unsustained Tachycardia Trial (MUSTT). Methods and Results-We analyzed the ECGs of 1638 patients from MUSTT who did not receive antiarrhythmic therapy (antiarrhythmic medication or implantable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 18 publications
4
94
0
4
Order By: Relevance
“…An annual all-cause mortality and sudden death of 4.7% and 2%, respectively, were observed in our study, which is similar to previous reports [3,5,21]. Some studies have shown that BFB per se is an independent risk factor of mortality [12][13][14], whereas others have reported that BFB merely reflects underlying heart disease, explaining the higher mortality rate in this population [3,6,7,15]. While only a limited number of clinical variables and investigations have been examined in some studies [3,6], the follow-up period in other studies has not been long enough to study the natural history regarding mortality [7,12,13].…”
Section: Discussionsupporting
confidence: 92%
“…An annual all-cause mortality and sudden death of 4.7% and 2%, respectively, were observed in our study, which is similar to previous reports [3,5,21]. Some studies have shown that BFB per se is an independent risk factor of mortality [12][13][14], whereas others have reported that BFB merely reflects underlying heart disease, explaining the higher mortality rate in this population [3,6,7,15]. While only a limited number of clinical variables and investigations have been examined in some studies [3,6], the follow-up period in other studies has not been long enough to study the natural history regarding mortality [7,12,13].…”
Section: Discussionsupporting
confidence: 92%
“…No randomized trials Observational study: nonpredictive of arrhythmic death 48 No randomized trials Observational studies: predictive 57,58 and nonpredictive 59 of arrhythmic death Nonsustained VT Randomized ICD trials: no survival benefit (combined with LVEF) 17 Observational study: predictive of arrhythmic death 60 Randomized ICD trials: survival benefit (combined with LVEF and a positive EPS) 15 …”
Section: Qrs Durationmentioning
confidence: 99%
“…However, the association between prolonged QRSd and sudden cardiac death (SCD) is less certain (2)(3)(4). While the largest study to date examining the relationship of prolonged QRSd to SCD reported a significant independent association (4), other smaller studies have had inconsistent results (2,3).…”
Section: Introductionmentioning
confidence: 99%